2004
DOI: 10.1074/jbc.m310786200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transmembrane Segment 8 of the GLUT1 Glucose Transporter by Cysteine-scanning Mutagenesis and Substituted Cysteine Accessibility

Abstract: The GLUT1 glucose transporter has been proposed to form an aqueous substrate translocation pathway via the clustering of several amphipathic transmembrane helices (Mueckler, M., Caruso, C., Baldwin, S. A., Panico, M., Blench, I., Morris, H. R., Allard, W. J., Lienhard, G. E., and Lodish, H. F. (1985) Science 229, 941-945). The possible role of transmembrane helix 8 in the formation of this permeation pathway was investigated using cysteine-scanning mutagenesis and the membrane-impermeant sulfhydryl-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 32 publications
1
33
1
Order By: Relevance
“…The latter 2 sites of transport might both contribute to the observed neurological symptoms, since they are both involved in the delivery of glucose to nerve cells. It is conceivable that the energy demand increases under conditions of prolonged exercise and exceeds the energy supply, which is reduced in PED patients with GLUT1 mutations, as shown by our uptake experiments and by previous functional studies of the mutated sites (30,31). This hypothesis is supported by the therapeutic success of both intravenously administered glucose during exercise and a permanent ketogenic diet, which changes the main energy source of the brain from glucose to ketone bodies, as observed in the index patient of family PED1 and his older son.…”
Section: Discussionmentioning
confidence: 54%
“…The latter 2 sites of transport might both contribute to the observed neurological symptoms, since they are both involved in the delivery of glucose to nerve cells. It is conceivable that the energy demand increases under conditions of prolonged exercise and exceeds the energy supply, which is reduced in PED patients with GLUT1 mutations, as shown by our uptake experiments and by previous functional studies of the mutated sites (30,31). This hypothesis is supported by the therapeutic success of both intravenously administered glucose during exercise and a permanent ketogenic diet, which changes the main energy source of the brain from glucose to ketone bodies, as observed in the index patient of family PED1 and his older son.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, a number of investigators have shown that cellular metabolism and ATP availability play a significant role in regulating GLUT1 expression and function through both direct and indirect mechanisms. Another report suggests that direct interaction of ATP with GLUT1-specific peptide sequences can lead to conformational changes that modulate transport of glucose and inhibit degradation of GLUT1 (18,35,36). Moreover, studies in skeletal muscle have shown that expression of a constitutively active form of AMP kinase (AMPK) results in increased GLUT1 and GLUT4 protein levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…45,62,63 Cysteine scanning mutagenesis was subsequently employed to probe which residues lined this proposed central pore. [64][65][66][67][68][69][70][71][72][73][74] The resulting model indicated that TMs 2, 4, 5, 7, 8, 11, and possibly 1 and 10 formed a central aqueous transport channel for glucose, whereas TMs 3, 6, 9, and 12 formed a structural scaffold on the outside of the protein. 70 A possible substrate binding site was also proposed, involving Q161, Q282, and W412.…”
Section: Structure Of Human Glut1mentioning
confidence: 99%